SMART TECHNOLOGIES (WIKI AND PODCASTS) IN FOREIGN LANGUAGE TEACHING - Tatiana L. Gerasimenko; Iliya V. Grubin; Tatiana M. Gulaya; Olga N. Zhidkova; Svetlana A. Romanova (Статистика и экономика, 2016)
The article focuses on smart learning technologies such as wiki, video and audio podcasts which are used both online and offline in a foreign language teaching process. These technologies are applied to complement traditional methods of teaching, enhance the learning motivation of students, provide them with possibilities to realize their intellectual and creative potential.